Small-signal stability in renewable-dominated grids: a comparative analysis of GFL and GFM storage for clustered PV mitigation - Altarjami, Ibrahim (Frontiers in Energy Research, 2025)
With the shift toward renewable-dominant power systems, concerns about small-signal stability have intensified, driven by reduced inertia and the loss of inherent damping formerly provided by synchronous machines. These challenges are amplified in aggregated networks and clustered photovoltaic (PV) installations, where the likelihood of poorly damped oscillatory modes increases especially in weak grids. Inverter-based energy storage can mitigate these issues, but its effectiveness depends critically on the control paradigm. This paper compares grid-following (GFL) and grid-forming (GFM) energy storage for mitigating small-signal instability in renewable-rich grids with clustered PV. A dynamic test system with high PV penetration is modeled, and its oscillatory behavior is assessed using eigenvalue and modal analyses. The study evaluates two configurations, GFL-integrated storage and GFM-integrated storage across varying penetration levels and grid strengths. Both approaches enhance stability, but GFM consistently achieves superior damping, with eigenvalues shifting deeper into the stable region. GFL provides moderate improvement yet remains vulnerable under weak-grid (low short-circuit strength) conditions due to phase-locked loop dynamics. Overall, GFM is more effective at suppressing oscillatory interactions, particularly in clustered PV settings. While GFL integration is simpler and broadly applicable, its stability-enhancement potential is weaker in renewable-intensive systems. These findings offer practical guidance for system operators and planners.